Workshop Pembuatan Alarm Air Sederhana Berbasis Transistor Sebagai Media Pembelajaran Fisika Di SMA Muhammadiyah 23 Jakarta - Martin Martin; Kusmajid Abdullah; Tri Isti Hartini (Jurnal SOLMA, 2021)
Program Kemitraan Masyarakat has been carried out with the title Workshop of Making Transistor-Based Simple Water Alarms as a Learning Media for Physics at SMA Muhammadiyah 23 Jakarta. This workshop was attended by 20 participants from grade 10 IPA students of SMA Muhammadiyah 23 Jakarta. The methods used in this service activity are: lecture method, discussion and direct practice but due to the Covid 19 pandemic, the method used has become an online method and periodic guidance through the WA group. The purpose of this workshop activity is so that students are able to understand electrical physics lessons through hands-on practice and students can also create real learning media. The result of this service is that students can increase their knowledge of how to make a project of tools that are applicable to physics. Through this PKM activity, it can open students' insights about higher education, especially in fields they are interested in such as Physics.